[18F] Sodium Fluoride Dose Reduction Enabled by Digital Photon Counting PET/CT for Evaluation of Osteoblastic Activity - Menendez, Maria I.; Moore, Richard R.; Abdel-Rasoul, Mahmoud; Wright, Chadwick L.; Fernandez, Soledad; Jackson, Rebecca D.; Knopp, Michael V. (Frontiers in Medicine, 2022)
The aim of the study was to assess the quality and reproducibility of reducing the injected [18F] sodium fluoride ([18F]NaF) dose while maintaining diagnostic imaging quality in bone imaging in a preclinical skeletal model using digital photon counting PET (dPET) detector technology. Beagles (n=9) were administered three different [18F]NaF doses: 111 MBq ( n=5), 18.5 MBq (n=5), and 1.9 MBq (n=9). Imaging started ≃ 45 minutes post-injection for ≃30 minutes total acquisition time. Images were reconstructed using Time-of-Flight, ultra-high definition (voxel size of 1x1x1 mm3), with 3 iterations and 3 subsets. Point spread function and Gaussian filtering were applied. Skeleton qualitative and quantitative molecular image assessment was performed. The overall diagnostic quality of all images scored excellent (61%) and acceptable (39%) by all the reviewers. [18F]NaF SUVmean showed no statistically significant differences among the three doses in any of the region of interest assessed. This study demonstrated that a 60-fold [18F]NaF dose reduction was not significantly different from the highest dose, and it had not significant effect on overall image quality and quantitative accuracy. In the future, ultra-low dose [18F]NaF dPET/CT imaging may significantly decrease PET radiation exposure to preclinical subjects and personnel.